2011
DOI: 10.1002/eji.201141863
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the T‐cell‐mediated autoimmune attack on CNS myelin in a new primate EAE model induced with MOG34–56 peptide in incomplete adjuvant

Abstract: Induction of experimental autoimmune encephalomyelitis (EAE) has been documented in common marmosets using peptide 34-56 from human myelin/oligodendrocyte glycoprotein ) in incomplete Freund's adjuvant (IFA). Here, we report that this EAE model is associated with widespread demyelination of grey and white matter. We performed an in-depth analysis of the specificity, MHC restriction and functions of the activated T cells in the model, which likely cause EAE in an autoantibody-independent manner. T-cell lines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 35 publications
3
69
0
Order By: Relevance
“…Data obtained in an equivalent nonhuman primate EAE model, the rhMOG-induced model in marmosets, show that the core pathogenic T cells are derived from effector memory cells present in the natural repertoire (32). Thus, we tested cellular and humoral immune responses against rhMOG to determine whether blockade of T cell costimulation via CD28 with FR104 might affect the generation of pathogenic cells.…”
Section: Immune Responses To Rhmogmentioning
confidence: 99%
“…Data obtained in an equivalent nonhuman primate EAE model, the rhMOG-induced model in marmosets, show that the core pathogenic T cells are derived from effector memory cells present in the natural repertoire (32). Thus, we tested cellular and humoral immune responses against rhMOG to determine whether blockade of T cell costimulation via CD28 with FR104 might affect the generation of pathogenic cells.…”
Section: Immune Responses To Rhmogmentioning
confidence: 99%
“…This implies that LCV-infected B cells suppress the activation of naive T cells; however, the constitutively expressed CD70 molecules on mouse DCs relay strong in vivo activation signals to T cells via homodimeric CD27 receptors (50). We reported previously that CD27 is expressed by autoaggressive MOG34-56-specific CTLs induced in the marmoset EAE model (9). Ligand binding to CD27 complements CD28 in determining the size of CD8 + effector memory T cell populations (51).…”
Section: Discussionmentioning
confidence: 99%
“…+ CTLs (7)(8)(9). Intriguingly, when marmosets were immunized with recombinant human MOG (rhMOG), representing the full-length extracellular domain , formulated with IFA, we observed only T cell activation against the MOG24-36 epitope (10).…”
mentioning
confidence: 94%
“…We further characterized these late-appearing T cells in marmosets immunized with peptide MOG34-56 formulated with IFA, in which clinical signs and widespread demyelination of white and grey matter developed without the induction of myelin-binding autoantibodies (Jagessar et al, 2010). It was shown that the T cells are specific for the MOG40-48 epitope, which is presented via MHC class I/Caja-E molecules; that the responding T cells have an NK-CTL (natural killer-cytotoxic T lymphocyte) phenotype (CD3 + CD8 + CD56 +); and that they display cytotoxic activity against EBV-infected B cells pulsed with MOG34-56 (Jagessar et al, 2012a). This type of T cells has been found in humans in the repertoire of effector memory T cells that keep chronic latent infection with CMV under control (Pietra et al, 2003).…”
Section: Modeling the T Cell Response To Injurymentioning
confidence: 99%
“…NK-CTLs against the MOG epitope 40-48 seem to play an important role in late-stage disease. These T cells can be induced by immunization of marmosets with MOG peptide 34-56 in IFA (Jagessar et al, 2012a), a condition where myelinbinding antibodies are not formed (Jagessar et al, 2015). The pathogenic role of these cytotoxic cells in MS is not exactly clear.…”
Section: Eae Development In Marmosets Involves Two Pathwaysmentioning
confidence: 99%